Cambios en la concentración sérica de hierro “libre” en niños con desnutrición aguda grave bajo tratamiento de recuperación nutricional. Turbo -Colombia (2005)
ABSTRACT: Iron suplementation is recomended for children with severe mal nutrition (Kwashiorkor), when they have recovered the apetite after nutritional support. However there is evidence suggesting that even when the apetite has been recovered, children still present serum “free” iron traces. Objective: To evaluate serum “free” iron, transferrin, and ferritin levels in children with severe malnutrition (kwashiorkpor) in two different periods of time: at baseline before the nutritional therapy starts, and the moment when children recover the apetite. Methods and materials: Longitudinal, prospective study was setting in Turbo-Antioquia. A total of 40 children aged < 5 Y, who 20 presented marasmus and 20 kwashiorkor. Meassurements like: serum “free” iron by capillary electrophoresis, serum transferrin, total proteins, albumin, iron and C-reactive protein (CRP) were obtained at baseline, and the time when children recover the apetite. Longitudinal analysis was used to evaluate changes in the malnourished group. Results: No significant diferences were found in both groups of malnourish children who had serum free iron before at baseline, and when they recieved nutritional treatment and recovered the appetite. Eventhought significant decrease on Serum free iron level were observed in both groups, there was some remanent trace of the metal in serum. Significant decrease on PCR level was also obtained and serum ferritin level stayed high in the edematous group when they recovering the apetite. Conclusions: Iron supplement is not recomended for children who had recovered the apetite, because they continuing presenting edema and some level of serum “free” iron, low transferrin and high ferritin levels. Iron suplement should be given when edema and infection have disappeared.